Impact of prairie fragment size on proportion of females and reproductive success of Lobelia spicata Lam., a gynodioecious species. (6th December 2019) - Byers, D. L.
Abstract: Due to ongoing human impacts, plant species increasingly occur in landscapes that are highly fragmented, with remaining natural habitats occupying small areas, resulting in populations that are smaller and more isolated than in previous time periods. This changed metapopulation structure is expected to have negative impacts on seed production. For example, the proportion of female plants within gynodioecious populations may be more volatile due to genetic drift in small populations associated with small habitat fragments, with concomitant impacts on seed production. My aims were to determine: (i) if variation in proportion of females is larger in smaller fragments; and (ii) if such changes in female frequency in small fragments result in reduced seed production. Thirty‐two populations of Lobelia spicata Lam., a gynodioecious species, were surveyed in 2000, 2001 and 2009 in the tallgrass prairie region of Midwestern North America (Illinois and Indiana, USA). Data were collected for: proportion of female plants, total number of flowering plants (measure of population size), seed set per plant and prairie fragment size (another measure of population size). The proportion of females is more variable in smaller prairie fragments. Seed number per fruit decreases as the proportion of females increases in a population, but only significantly for female plants. The number of flowering plants is positively associated with fruit production for both genders. Populations within larger prairie fragments have higher seed production. The reproductive consequences of habitat fragmentation depend on the plant breeding system. While both sexes were negatively impacted, females were more adversely affected. Abstract : Lobelia spicata Lam., a gynodioecious prairie species occurring in the highly fragmented prairies of Midwestern North America, was found to have greater variation in female plant frequency as habitat size declined.